Pengaruh Peran Staf Operasi Mabes TNI Menyiapkan Satgas UNIFIL Guna Meningkatkan Kepercayaan PBB - Horiyanto, Horiyanto; Sumantri, Rudy; Lusiani, Fauma (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
This research aims to analyze the influence of the role of the TNI Headquarters operations staff in preparing the UNIFIL (United Nations Interim Force in Lebanon) Task Force and its impact on increasing the UN's trust in Indonesia in supporting international peacekeeping missions. This study uses a qualitative approach with a case study method, involving in-depth interviews with members of the TNI Headquarters, observation of the Task Force preparation process, and analysis of related documents. The results show that the TNI Headquarters operations staff has a crucial role in preparing the UNIFIL Task Force, which includes inter-institutional coordination, personnel training, logistics procurement, and fulfillment of UN-established operational standards. The study found that strengthening the operations management system and continuous training for operations staff are key to improving mission effectiveness. this study recommends enhancing cooperation among relevant agencies and updating the training system to align with the dynamics of global peacekeeping missions.